Von Willebrand factor antigen (vWF-Ag): A non-invasive predictor of treatment response and serious adverse events in HCV patients with interferon triple therapy. Issue 10 (October 2016) - Rutter, Karoline; Etschmaier, Alexandra; Ferlitsch, Monika; Maieron, Andreas; Hametner, Stephanie; Horvatits, Thomas; Paternostro, Rafael; Salzl, Petra; Reiberger, Thomas; Peck-Radosavljevic, Markus; Quehenberger, Peter; Hofer, Harald; et al.
Abstract: Background: Treatment of chronic hepatitis C virus (HCV) infection was revolutionized within the last years. Interferon free antiviral regimens are not accessible without limitations. Combination of peginterferon/ribavirin with first generation direct acting antivirals is less effective and associated with serious adverse events. Aim: We have shown that vWF-Ag is associated with portal hypertension and treatment response to PEG/RBV and we evaluated if vWF-Ag is a predictive marker for treatment response and safety in patients with triple therapy. Methods: 222 HCV-GT 1 patients and DAA based triple therapy were included in this retrospective, multicenter study. Results: Median vWF-Ag levels were 167.0% [IQR: 124.0–210.0%]. Significantly higher levels were seen in patients without SVR; median 190% [IQR: 146.0–259.5%] versus SVR: 142.5% [IQR: 114.3–196.8%], p < 0.001. Furthermore levels of vWF-Ag were identified as independent predictor of non SVR; (OR: 1.009; 95%CI: 1.016–1.3, p = 0.005). In patients with cirrhosis elevated vWF-Ag levels were associated with increased incidence of SAEs (OR: 1.016; 95%CI: 1.004–1.028; p = 0.007). Best cut off for prediction of SAEs was vWF-Ag > 281.5% with a sensitivity of 78% and a specificity of 90%. Conclusion: Baseline vWF-Ag levels predict outcome of DAA based treatment in HCV-1 patients and identify patients with a risk of SAEs. Therefore vWF-Ag may be an additional marker for selecting patients for interferon free therapeutic regimens.